IJCM_337A: Prevalence Of Social Anxiety Disorder Among Adolescents In Ernakulam District, Kerala - Moidu Mufeeda; Mohandas Sreelakshmi (Wolters Kluwer Medknow Publications, 2024)
Background: Social anxiety disorder (SAD), a prevalent form of anxiety disorder is a chronic, disabling and treatable one with common onset in adolescence. Individuals experiencing SAD exhibit symptoms of anxiety or fear in circumstances where they could face scrutiny, evaluation, or judgment from others. Objective: The primary objective of the study was to determine the prevalence of SAD among adolescents in Ernakulam district, Kerala. The secondary objectives were to compare the prevalence of SAD among urban and rural adolescents and to determine the factors associated with SAD among adolescents in Ernakulam district, Kerala. Methodology: School based cross-sectional study was done among 474 students from schools of Ernakulam district, Kerala. Students were enrolled using multi-stage sampling method. A semi structured questionnaire consisting of sociodemographic details and Social Phobia Inventory (SPIN) was administered to the participants by face-to-face interview after attaining the necessary assent and consent. Results: The overall prevalence of SAD among the study participants was 19.6% with the prevalence of SAD among the urban and rural students being 17.6% and 22.9% respectively. Having to give speeches was the most common phobia in majority (40.9%) of participants. Female sex [aOR=2.02(1.26-3.21); p=0.003] was found to be a determinant of SAD in the study population. Age, type of family, number of family members, place of residency were not statistically associated with SAD in this study Conclusion: The current study showed that 1/5th of the study population had social anxiety disorder. With appropriate intervention through health education and psychotherapy, its progression can be effectively impeded.